Involvement of forebrain imidazoline and alpha(2)-adrenergic receptors in the antidipsogenic response to moxonidine - Andrade, CAF; Oliveira, L. B.; Martinez, G.; Silva, DCF; De Luca, L. A.; Menani, José Vanderlei [UNESP] (New York Acad Sciences, 2003)
We investigated the participation of central alpha(2)-adrenoceptors and imidazoline receptors in the inhibition of water deprivation-induced water intake in rats. The alpha(2)-adrenoceptor and imidazoline antagonist idazoxan (320 nmol), but not the alpha(2)-adrenoceptor antagonist yohimbine, abolished the antidipsogenic effect of moxonidine (alpha(2)-adrenoceptor and imidazoline agonist, 20 nmol) microinjected into the medial septal area. Yohimbine abolished the antidipsogenic effect of moxonidine intracerebroventricularly. Therefore, central moxonidine may inhibit water intake acting independently on both imidazoline receptors and alpha(2)-adrenoceptors at different forebrain sites.
Keywords: thirst; angiotensin II; dehydration; water intake